Effect of Hydroxychloroquine on Antiphospholipid Antibody‐Induced Changes in First Trimester Trophoblast Function. (11th December 2013) - Albert, Caroline R.; Schlesinger, William J.; Viall, Chez A.; Mulla, Melissa J.; Brosens, Jan J.; Chamley, Lawrence W.; Abrahams, Vikki M.
<x xml:space="preserve">Abstract</x> Problem Women with antiphospholipid syndrome (APS) are at risk for pregnancy complications. Antiphospholipid antibodies (aPL) alter trophoblast function by triggering an inflammatory cytokine response; modulating angiogenic factor secretion; and inhibiting migration. While patients with APS are often treated with hydroxychloroquine (HCQ), its effect on trophoblast function is poorly understood. Method of study A human first trimester trophoblast cell line was treated with or without antihuman β2GPI mAbs in the presence or absence of HCQ. Supernatants were analyzed by ELISA. Cell migration was measured using a colormetric assay. Results Antiphospholipid antibodies‐induced trophoblast IL‐8, IL‐1 β, PlGF, and sEndoglin secretion were not altered by HCQ. aPL‐induced inhibition of trophoblast migration was partially reversed by HCQ, even though HCQ significantly increased secretion of pro‐migratory IL‐6 to greater than baseline. aPL‐induced upregulation of TIMP2 appears to inhibit trophoblast migration; the inability of HCQ to prevent aPL‐induced TIMP2 may explain why migration was only partially restored. Conclusion Hydroxychloroquine reversed the aPL‐inhibition of trophoblast IL‐6 secretion and partially limited aPL‐inhibition of cell migration. Thus, some form of combination therapy that includes HCQ may be beneficial to pregnant APS patients.